Disseminated cysticercosis: rare manifestation of a common disease. (18th December 2012) - Singh, Neha; Singh, Deepak Kumar; Parihar, Anit; Singh, Ragini
Abstract : We are presenting a case of disseminated cysticercosis involving the brain, spinal cord, orbit, muscles, subcutaneous tissues, liver and spleen of an immunocompetent man. Although cysticercosis is a common tropical disease, such widespread dissemination is an uncommon manifestation. Imaging studies are described with emphasis on hepatic and splenic involvement which has been described only rarely in the published literature.